WHY FINANCIAL INDEPENDENCE IS CRUCIAL FOR WOMEN - Norboyeva Zuhraxon Alijon qizi (TADQIQOTLAR, 2025)
Abstract:  This  article  looks  at  how  women's  financial  independence  has changed throughout time, what obstacles they face now, and how financial autonomy affects women's well-being. The government's efforts to close the gender wage gap and encourage  women's  economic  involvement  are  highlighted  by  case  studies  from Australia,  New  Zealand,  and  Uzbekistan.  Cultural  traditions,  pay  disparity,  and restricted  access  to  financial  resources  continue  to  impede  women's  financial independence  despite  continuous  attempts.  For  women  to  have  equal  access  to economic  possibilities,  the  essay  highlights  the  necessity  of  workplace  diversity, financial  education,  and  regulatory  changes.  Achieving  financial  independence advances social and economic advancement in addition to being crucial for gender equality.